A practical method for the rapid detection and structural characterization of major constituents from traditional Chinese medical formulas: analysis of multiple constituents in Yinchenhao Decoction1. Issue 11 (7th June 2015) - Fu, Zhiwen; Li, Zhixiong; Hu, Pei; Feng, Qin; Xue, Rui; Hu, Yiyang; Huang, Chenggang
<x xml:space="preserve">Abstract</x> A rapid characterization process of major constituents from Yinchenhao Decoction using FBF algorithms.